Local inner ear application of dexamethasone in cochlear implant models is safe for auditory neurons and increases the neuroprotective effect of chronic electrical stimulation. - Verena Scheper; Roland Hessler; Mareike Hütten; Maciej Wilk; Claude Jolly; Thomas Lenarz; Gerrit Paasche (PLoS ONE, 2017)
Dexamethasone (DEX) can reduce fibrous tissue growth as well as loss of residual hearing which may occur after cochlear implantation. Little is known about the effect of local inner ear DEX treatment on the spiral ganglion neurons (SGN), which are the target of the electrical stimulation with a cochlear implant (CI). Three different clinically relevant strategies of DEX-delivery into the inner ear were used. DEX was either eluted from the electrode carriers' silicone, released from a reservoir by passive diffusion, or actively applied using a pump based system. The effect of the locally applied DEX on SGN density, size and function was evaluated. DEX did not affect the SGN density compared to the relevant control groups. Simultaneously applied with chronic electrical stimulation (ES), DEX increased the neuroprotective effect of ES in the basal region and the hearing threshold tended to decrease. The EABR thresholds did not correlate with the relevant SGN density. When correlating the SGN number with fibrosis, no dependency was observed. DEX concentrations as applied in these animal models are safe for inner ear delivery in terms of their effect on SGN density. Additionally, DEX tends to improve the neuroprotective effect of chronic electrical stimulation by increasing the number of surviving neurons. This is an important finding in regard to clinical applications of DEX for local treatment of the inner ear in view of cochlear implantation and other applications.